2008
DOI: 10.1596/1813-9450-4500
|View full text |Cite
|
Sign up to set email alerts
|

Health And Civil War In Rural Burundi

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 3 publications
4
109
0
Order By: Relevance
“…Bundervoet et al (2008) find that children exposed to the 1994-96 civil war in Burundi have -.34 height-for-age z-scores lower. Alderman et al (2006) also find that children exposed to the civil war and drought shocks in Zimbabwe are 3.4 cm shorter several years later in adult life.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Bundervoet et al (2008) find that children exposed to the 1994-96 civil war in Burundi have -.34 height-for-age z-scores lower. Alderman et al (2006) also find that children exposed to the civil war and drought shocks in Zimbabwe are 3.4 cm shorter several years later in adult life.…”
Section: Discussionmentioning
confidence: 74%
“…He finds that exposed pregnant women are more vulnerable to influenza and had more still births. On the impacts of conflict, Bundervoet et al (2008) study the effects of the civil war in rural Burundi. They find that children born in provinces affected by the war had on average 0.5 standard deviations lower height-for-age z-scores than non-exposed children.…”
Section: Literature On Shocksmentioning
confidence: 99%
“…At the time of the last survey in 2011, the civil war had just ended. The aftermath of the civil war, mainly in the North, involved theft of livestock, destruction of public infrastructures and crops, shortage of human resources, economic contraction, and displacement of health staff and populations towards the southern parts (44)(45)(46) . A recent study in Côte d'Ivoire provided evidence that children from conflict-affected regions (South-West, West, North-West, North, Abidjan, North-East regions) or households having experienced economic stress during the period 2002-2007 (measured by loss of productive assets such as jobs, farms and livestock, or a decrease in income) had lower mean HAZ than those from less conflict-affected regions (47) .…”
Section: Discussionmentioning
confidence: 99%
“…But the long-term destructive effects of violent conflict may remain entrenched in certain regions and among some population groups even if economic growth converges at the aggregate level. Recent research on the micro-level effects of violent conflict has shown that the negative impact of conflict on educational outcomes, labor market participation and 7 health status of individuals and households may be observed decades after the conflict (Akbulut-Yuksel 2009; Akresh and de Walque 2008;Alderman, Hoddinott and Kinsey 2006;Bundervoet, Verwimp and Akresh 2009;Ibáñez and Moya 2009;Shemyakina 2010). Although these effects may average out at the aggregate level, they may contribute to the emergence of poverty traps among specific groups affected by violence (Justino 2009(Justino , 2010a.…”
Section: Figuresmentioning
confidence: 99%
“…Shemyakina (2010) finds that exposure to the Tajik conflict, as measured by physical damage to households' dwellings, had a significant and negative effect on the enrolment of girls. She observes little or no effect on the enrolment of boys, and 2 See Alderman et al (2006) for Zimbabwe, Bundervoet et al (2009) for Burundi, Akresh and Verwimp (2006), Akresh, Verwimp and Bundervoet (2007) and Akresh and de Walque (2008) for Rwanda and Guerrero-Serdán (2009) for Iraq. postulates that households affected by conflict invested more in the schooling of boys because it may make more economic sense to educate boys.…”
Section: Figuresmentioning
confidence: 99%